Local Economy And Tourism Destination Competitiveness: A Bibliometric Co-Occurrence Analysis Using Vosviewer - Muhammad Abrar; Muhammad Aris Muladi (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2026)
Strengthening the local economy is a key element in enhancing the competitiveness of tourism destinations, particularly in the context of global dynamics, sustainability pressures, and changing tourist preferences in the post-pandemic era. Although research on local economies and tourism destination competitiveness has continued to grow, the existing literature remains fragmented and has not been systematically mapped. This study aims to examine the intellectual structure, research trends, and major thematic clusters in the literature on local economy and tourism destination competitiveness through a Systematic Literature Review (SLR) supported by bibliometric analysis. Data were collected from the Dimensions AI database, limited to peer-reviewed and indexed journal articles published between 2019 and 2025. The analysis was conducted using VOSviewer to map keyword co-occurrence, network, overlay, and density visualizations. The findings reveal several dominant thematic clusters, including (1) local economy and community empowerment, (2) sustainable tourism and destination competitiveness, (3) community-based tourism and local wisdom, and (4) policy, governance, and innovation in destination development. Overlay visualization indicates a shift in research focus from conceptual discussions toward more applied and practice-oriented approaches emphasizing sustainability, stakeholder collaboration, and the integration of the creative economy. These results confirm that strengthening the local economy through sustainable practices and community participation plays a strategic role in enhancing tourism destination competitiveness. This study contributes by providing a comprehensive scientific mapping that can serve as a reference for researchers, practitioners, and policymakers in formulating inclusive, competitive, and sustainable tourism development strategies.